Analysis of students’ mathematical Problem Solving Ability on Integers Materials (Unnes Journal of Mathematics Education Research, 2022)
The goal of this study was to evaluate how well students could solve mathematical problems involving integer material. 24 students in grade VII at SMP YPII Bungur Bekasi participated in this study during the 2022–2023 academic year. Five written exam items, observation, and interviews with students and math teachers at the school were used to collect the data. According to the analysis' findings, SMP YPII Bungur Bekasi pupils in the seventh grade have the necessary capacity to solve mathematical problems including integer content. The evaluation of pupils' abilities to respond to the questions was fairly successful. According to an average estimate of students' problem-solving skills, SMP YPII Bungur Bekasi students have a rate of 63.1%. Some students, meanwhile, are still having trouble figuring out the issue at hand. Several factors, including (1) students' lack of attention to the material being explained by the teacher, (2) students' lack of understanding of the material presented, and (3) lack of student interest in relearning the material that had been described, were to blame, according to the interviews that were conducted. The degree of ability results gained are also influenced by the educational environment, which includes outsiders.